2016
DOI: 10.1007/s00408-016-9926-8
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of CT Pulmonary Artery Diameter for Pulmonary Hypertension in End-Stage COPD

Abstract: IntroductionPulmonary hypertension (PH) in COPD is associated with a higher mortality and an increased risk on exacerbations compared to COPD patients without PH. The aim was to evaluate the diagnostic value of pulmonary artery (PA) measurements on chest computed tomography (CT) for PH in end-stage COPD.MethodsCOPD patients evaluated for eligibility for lung transplantation between 2004 and 2015 were retrospectively analyzed. Clinical characteristics, chest CTs, spirometry, and right-sided heart catheterizatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 31 publications
2
10
0
Order By: Relevance
“…In patients with severe COPD, an mPA diameter ≥30 mm has been associated with PH [11]. In our study, all 3 patients with an RVSP >50 mm Hg had mPA and pPA diameters ≥30 mm.…”
Section: Discussionsupporting
confidence: 48%
See 2 more Smart Citations
“…In patients with severe COPD, an mPA diameter ≥30 mm has been associated with PH [11]. In our study, all 3 patients with an RVSP >50 mm Hg had mPA and pPA diameters ≥30 mm.…”
Section: Discussionsupporting
confidence: 48%
“…Since only 3 patients in our cohort had an RVSP >50 mm Hg, the sample size was too small to calculate sensitivity and specificity for the different PA diameters. Therefore, we used the threshold of a PA diameter ≥30 mm based on an earlier study [11]. In this study, a PA diameter ≥30 mm was shown to have the highest positive and negative predictive value in the detection of PH in patients with severe COPD.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similary, Sanal et al observed in a retrospective study among patients with pulmonary embolism (mean age 59 ± 15 years) that a PA/AA ratio ≥ 1.0 had a 59% sensitivity, 82% specificity, a 55% positive predictive value, and a 84% negative predictive value for diagnosing moderate to severe PH defined as a pulmonary artery systolic pressure ≥ 50 mmHg on Doppler Echo ( 13 ). Mohamed Hoesein et al ( 14 ) assessed the accuracy of CT PA diameter and PA/AA ratio for PH in end-stage COPD among 92 patients (mean age 55 years) and found that a PA/AAratio >1 had a negative predictive value of 77.9% and a positive predictive value of 63.1%. However, the results of the present study would suggest that in an elderly patient population, such as those selected to undergo TAVI, a PA/AA ratio ≥ 1.0 would not be sensitive enough as we observed a sensitivity of just 4.4% when PA/AA ratio ≥ 1.0 was used to predict the presence of PH.…”
Section: Discussionmentioning
confidence: 99%
“…Usually, MAP widest dimension is measured on axial CT images, on inspiratory acquisition, at bifurcation level, and, AO is measured on the same image 107,108,111,112. Descending aorta is also measured at the same level.112 Thresholds values to detect PH in COPD patients are: MAP ≥29 mm21,113,114 and MAP/AO>1 107,110,111,115,116Figure 3Pulmonary artery and aorta measurements.…”
Section: Central Vesselsmentioning
confidence: 99%